A paper in the hand is worth two in the bush. Contribution of literature to the production of scientific papers - Cartay, Rafael (2018)
Participants in scientific research paper writing workshops often raise concerns regarding the different sections of the structure of the paper: title, abstract, introduction, methodology, content, and discussion. Since scientific findings must be conveyed clearly, briefly, and in a coherent style, I propose that scientists interested in properly transmitting such knowledge benefit from the help of writers, whose primary purpose is to convey to the reader, in a clear and enjoyable manner, the descriptions of landscapes, moods, and the thoughts and actions of their fictional characters.